(untitled) (Journal of Organizational Psychology, 2020)
This article claims that neither indeterminism nor the so-called neuro-determinism provides an adequate response to the problem of criminal responsibility, highlighting the non-apprehensibility of the problem of freedom and the non-dehumanized image of man. At the same time this contribution proposes a solution from the point of view of humanist compatibilism based on some key assumptions and methodological anchors, such us the rejection of retributivism and the search for unified scientific responses.